COMPARATIVE ANALYSIS OF GASEOUS FUELS COMBUSTION HEAT - Voronova, Ye.; Pozdnyakova, O.; Ilіuyshchenko, A.; Воронова, Е. М.; Позднякова, Е. И.; Илющенко, А. Н.; Воронова, Є. М.; Позднякова, О. І.; Ілющенко, А. М. (Харьковский национальный автомобильно-дорожный университет, 2011)
The estimation of the calorific value of gaseous fuels such as pyrolysis gas, biogas, landfill gas, natural shale gas was done. The results showed that the calorific value of pyrolysis gas was comparable to the calorific value of biogas and shale gas.
СРАВНИТЕЛЬНЫЙ АНАЛИЗ ТЕПЛОТЫ СГОРАНИЯ ГАЗООБРАЗНЫХ ТОПЛИВ
ПОРІВНЯЛЬНИЙ АНАЛІЗ ТЕПЛОТИ ЗГОРЯННЯ ГАЗОПОДІБНИХ ПАЛИВ
Keywords: calorific value; pyrolysis gas; biogas; shale gas; utilization of tyres; теплотворная способность; пиролизный газ; биогаз; сланцевый газ; утилизация шин; теплотвірна здатність; піролізний газ; біогаз; сланцевий газ; утилізація шин; 678.027:658.567